Improving ecosystem services through urban agriculture and greening initiatives - Monson, Brooke Elizabeth (My University, 2025)
With the increase of urbanization, environmental degradation, and climate change, urban agriculture and urban green space initiatives have gained increasing attention for their roles in improving urban ecosystem services. This literature review discusses the role of urban agriculture in mitigating challenges associated with urbanization, while highlighting its role as an ecosystem service provider. Literature was selected and synthesized using keyword searches in academic search engines and grey literature. This review defines the four dimensions of ecosystem services, explores the environmental, cultural, and socioeconomic impacts of urban agriculture, and highlights the contributions of ecosystem services to ecological health, food security, and urban development. Additionally, the emerging trends in urban agriculture and urban green space research are highlighted, while noting the research gaps and barriers in adoption. Because this review contains several aspects of urban ecosystem services, it may limit the exploration of all service functions and benefits. It is important to recognize the multifunctional roles that urban vegetation plays in creating more resilient, sustainable cities.
Keywords: Urban agriculture; Ecosystem services; Urban green spaces; Supporting ecosystem services; Provisioning regulating services; Regulating ecosystem services; Cultural ecosystem services